From blueprint master plans to democratic planning in South Asian cities: Pursuing good governance agenda against prevalent patron-client networks - Khan, Shahed; Swapan, Mohammad (Elsevier, 2013)
Despite similar rhetoric and stated policies, there are major differences in urban planning and its implementation and management between cities of developed countries and those of the developing world. These differences are most evident in the degree of involvement of citizens in planning and urban governance processes. The degree of democratic traditions prevalent in these countries could partially explain these differences, stemming from historical factors and the evolutionary paths of urbanization followed by the countries and the resulting socio-economic and cultural condition. The multifaceted challenges and unpredictable political environment contribute to a complex nature of governance and participation. This article examines the nature of public participation in South Asian cities highlighting the tensions between representative democracy and participation in Bangladesh. The authors view the ‘orthodoxy’ of South Asian planning style steaming from a persistence of the blueprint master plan approach to planning as a major obstacle to true participation. The overall urban governance system in place is largely influenced (and often undermined) by a highly politicized bureaucracy with operates within complex patron–client networks created by bureaucrats and politicians for mutual benefits. With overwhelming numbers of urban poor and a general dearth of resources, these cities are highly dependent on foreign aid and so the planning agenda is, to a significant extent, donor-driven. The complexity of planning and urban governance is further intensified by remnants and legacies of the region’s colonial heritage that contribute to create a milieu of poor urban governance and entrenched corruption wherein opaque and non-participatory planning practices and processes are normally prevalent.The article sets out to identify the forces that are stifling participatory urban planning in Bangladesh, focussing on socio-economic disparity within cities and the ineffectiveness of the administrative setup. It also analyses the political system in terms of the influence of political parties as well as the role played by international aid/ donor agencies.